A pilot assimilation of glider data in TOPAZ3 - Sakov, Pavel (Zenodo, 2009)
TOPAZ3 is an operational sea-ice data assimilation system for North Atlantic and Arctic regions based on the HYCOM model and ensemble Kalman filter (EnKF). TOPAZ3 uses an ensemble of 100 model states that is integrated and updated in a weekly data assimilation cycle. Currently the the following observations are assimilated: altimetry SLA, altimetry SST, in-situ salinity (S) and temperature (T ) from ARGO profiles, sea ice concentration, and sea ice drift. The purpose of this report is the investigation of possibility and benefits from the assimilation of in-situ S and T data from gliders. The workflow was supposed to use the existing one for assimilating data from ARGO profiles, with the necessary modification to be made to account for variations in horizontal position. The in-situ glider observations can be used for producing a targeted hindcast of the ocean state at the time and location of interest. They can also be expected to have a larger impact in smaller scale system. Apart from being used for data assimilation, the subsurface observations by gliders represent a valuable oceanographic resource, particularly for the North Atlantic and Arctic region, due to the scarcity of subsurface observations in those regions. From data assimilation perspective, they may be used for verification purposes as well as for studying of the subgrid variability. NERSC Technical Report no. 308.